20. RELATIONSHIP BETWEEN EUPLOIDY RATES AND D5 KIDSCORE™ OF BLASTOCYSTS DERIVED FROM EMBRYOSCOPE. (August 2019) - Yap, W.Y.; Lee, C.S.S.; Lim, Y.X.; Lim, M.W.
Abstract : Introduction: Time-lapse microscopy (TLM) offers continuous monitoring of embryo development in an undisturbed culture condition, minimalising the stress imposed by changes in temperature, oxygen and pH in the culture medium; hence optimising culture environment. Moreover, the availability of morphokinetics assessment and annotation models such as KIDScore™ in TLM can help predict the implantation potential of an embryo. Several studies have also shown a reduction in pregnancy loss in IVF with TLM. However, the association between annotation models and euploidy rates has not been reported. This is a retrospective study to assess the relationship between euploidy rate and D5 KIDScore™ of blastocysts derived from IVF in Alpha Fertility Centre, Malaysia between January to December 2018. Material and Methods: Eight hundred and seven (807) patients (age ranged 25 – 45) had their embryos cultured to blastocyst stage. All blastocysts were cultured in Embryoscope™ according to the manufacturer's specifications (Vitrolife, Sweden). Any utilisable blastocysts were annotated and scored using D5 KIDScore™. Blastocysts scored between 1.0 – 5.9 were categorised as Group A while those scored between 6.0 – 9.9 were categorised as Group B. Three hundred and seventy-one (371) blastocysts from Group A and 1783 blastocysts from Group B which was at least fair grade (using Gardner blastocyst grading system) were biopsied and screened using Next Generation Sequencing (Ion Torrent, USA). The mean age of patients from Group A and B were 34.4 and 34.1 respectively (p>0.05). Results: The euploidy rate of blastocysts from Group A and B were 48.8 % and 59.3% respectively whereas the aneuploidy rate of blastocysts from Group A and B were 51.2% and 40.7% respectively. Both euploidy and aneuploidy rates between Group A and Group B were statistically significant (p=0.0002). Conclusions: This retrospective study demonstrates that blastocysts with a D5 KIDScore™ of 6.0 – 9.9 have a higher euploidy rate compared to blastocysts with a D5 KIDScore™ 1.0 – 5.9. It is thus recommended for patients who had time-lapse embryo monitoring without PGT-A to transfer blastocysts with a D5 KIDScore™ 6.0 – 9.9 in lieu of the higher euploidy rate. Nevertheless, further studies with a larger sample size should be performed to confirm the above.